Incidence of Ciguatoxin fish poisoning in Trivandrum, India - Rajisha, R.; Kishore, Pankaj; Panda, Satyen Kumar; Harikrishnan, G.; Ajitha, K. C.; Suresh, M. K.; Chowdhury, Labrechai Mog; Ravishankar, C. N.; Ashok Kumar, K. (Indian Journal of Fisheries, 2018)
Ciguatoxin (CTX) is a visibly unidentifiable, colourless, odourless, heat stable and lipid soluble polyether marine biotoxin associated with human illness. Marine dinoflagellates under the genus Gambierdiscus are responsible for producing ciguatoxins (CTX). The ciguatoxin gets accumulated in herbivorous fishes, gets biotransformed in carnivorous fishes and finally reach fish consumers. In January 2016, individuals who consumed red snapper in Trivandrum, Kerala, India were suspected to be intoxicated with ciguatera based on characteristic symptoms as assessed by medical team from Trivandrum Medical College, Kerala, India. The red snapper species was identified and confirmed as Lutjanus bohar by DNA barcoding. Mouse bioassay was carried out to detect the presence of ciguatoxin and the tested mice showed symptoms related to suspected CTX toxicity. Significantly higher level of ciguatoxin lethal dose was estimated which was found equivalent to 16.25 ng of CTX-1 which led to 13% of weight loss in tested mice. Medical professionals also investigated clinical manifestations of suspected toxicity in hospitalised individuals. This study indicated that there is a need for regular surveillance of seafood landed across the coast and consumer’s awareness for their safety.